Produire les échelles de la transition à Fessenheim : contingences et jeu d’acteurs autour de la fermeture d’une centrale nucléaire - Teva Meyer; Fanny Vallerand; Valentine Bour; Charlotte Dauwe; Valentine Erne-Heintz; Thomas Schellenberger (L'Espace Politique)
The permanent shut down of Fessenheim nuclear power plant in June 2020 had been preceded by the signature of a policy document, the Projet d’avenir du territoire de Fessenheim (PAT), which aims at ensuring its industrial reconversion. Drafted by the French administration’s services and local authorities, it introduces three spatial scales framing the post-nuclear transition. Mobilizing the case of Fessenheim, this paper offers to strengthen our knowledge of the politics of scales’ concrete practices within energy transitions by questioning (1) the impact of these three scales on the post-nuclear transition and (2) the sociopolitical dynamics leading to their production. By moderating the dominant constructivist approach to scales, sometimes criticized for its teleological nature, we focus on actors’ “scalecrafts”, understood as the messy craftwork, techniques, competences and difficulties underpinning all scalar assemblage. To do so, this paper is built on a corpus of regional newspaper’s articles and 46 semi-directive interviews with actors involved in the PAT’s production. Results show that these scales, which are effectively constraining the extend of the post-nuclear transition, relies on three dynamics: discursive strategies tending to naturalize and essentialize scales through the economization of the debates as well as legal interpretations; the politicization of the transition around the conflicting issue of tax losses’ compensation; and lobbying efforts by local authorities. We conclude by identifying seven entangled factors participating in the scales’ production. These results lead us to question the process of territorial denuclearization.